2016
DOI: 10.1108/ijchm-05-2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

The influence of e-word-of-mouth on hotel occupancy rate

Abstract: Purpose -Online reviews have become increasingly important for customer decisionmaking. The hotel industry represents a noticeable case. Consumer reviews posted on websites such as Bookings.com, TripAdvisor, and Venere.com play a critical role in consumers' choice of a hotel. For this reason a number of recent studies analyses different aspects of online reviews. The purpose of this paper is to investigate their effects in terms of hotel occupancy rates.Design/methodology/approach -The paper measures through r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
219
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(225 citation statements)
references
References 79 publications
(135 reference statements)
2
219
0
4
Order By: Relevance
“…This finds an echo in Hu, Kandampully, and Juwaheer () in that consumers who experienced the moderate quality of service were less inclined to report their experiences. Viglia et al () corroborated that this under‐reporting bias affects the reliability of online reviews.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finds an echo in Hu, Kandampully, and Juwaheer () in that consumers who experienced the moderate quality of service were less inclined to report their experiences. Viglia et al () corroborated that this under‐reporting bias affects the reliability of online reviews.…”
Section: Discussionmentioning
confidence: 92%
“…Also, (Öğüt & Onur Taş, ) found that 84% of all hotel guests use online reviews to help them plan their holidays. Furthermore, Nieto‐Garcia, Resce, Ishizaka, Occhiocupo, and Viglia () and Viglia, Minazzi, and Buhalis () argue that hotel managers should strive to understand the effect of consumers' attitude to online reviews on their decision making and in turn hotel performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sen and Lerman (2007), online consumer reviews are a type of word of mouth involving positive or negative statements given to the products by the consumers in online shopping malls. Moreover, Viglia et al (2016) showed that consumers often rely on outside sources such as customer reviews online due to limited direct information about the quality of service provided. In other words, credibility can be considered as the opinion of the people on the reality of the assessment (Erkan & Evans, 2016).…”
Section: Website Reputationmentioning
confidence: 99%
“…This article tries to fill this gap and helps incorporate research with the validity of reviews posted without verification procedures. Moreover, this article tries to provide additional insight into ANALYSIS OF HOTEL ONLINE REVIEWS 3 Booking.com are a popular online source for hotel information, as are social media websites like Trip Advisor and Facebook (Sun, Fong, Law & Luk, 2015), which draw the attention of researchers (Balagué, Martin-Fuentes, & Gómez, 2016;Viglia, Minazzi, & Buhalis, 2016).…”
Section: Introductionmentioning
confidence: 99%